Propuesta De Intervención Urbano Arquitectónica Del Actual Teatro Segundo Yánez Velasco Del Cantón San Miguel De Bolívar - Orozco Velasco, Josselyn Dayana (2023)
This research project focuses on the PROPOSAL FOR URBAN ARCHITECTURAL INTERVENTION OF THE CURRENT SEGUNDO YÁNEZ VELASCO THEATER OF SAN MIGUEL DE BOLÍVAR. Initially, an architectural element of great cultural value is analyzed that has been abandoned without activity for 10 years, that is located close to the historic area of the city, which shows and highlights the lack of social activity in the city.As well as the loss of an important artistic tradition: the theatrical works that took place in the building for many years, as well as the cultural propagation of the area. The project traces the origin of the city from the Spanish colonial era to its current state and proposes an urban intervention approach for a new prototype of a more humanized and diversified city. The study method is based on knowing, evaluating and proposing criteria that were used in the urban analysis, through this, significant elements in the urban fabric and areas that require intervention were highlighted, therefore a polygon that encompasses elements was identified. influential with the architectural project and creates a flow of activities throughout the area. The primary objective of the research is to generate a more dynamic city model oriented towards its inhabitants and visitors, seeking to transform public spaces into versatile places for daily activities and reinforce the intellectual expression of the locality in terms of history, art, music, culture and theater, in addition to promoting the revitalization of the theater as a significant cultural space that promotes the identity and tradition of the town.